Ablation behavior of glass fiber reinforced polybenzoxazine composites irradiated by high energy continuous-wave laser. (17th May 2019) - Ma, Chen; Ma, Zhuang; Gao, Lihong; Liu, Yanbo; Li, Hezhang; Lv, Yuwei; Wang, Fuchi
Abstract: Laser, especially high energy continuous-wave (CW) laser, can destroy traditional metal or polymer materials in an extremely short time. Although polybenzoxazine-based composites have been applied in many fields, its laser ablation behavior is still unclear. In this case, glass fiber reinforced polybenzoxazine composites are successfully prepared and irradiated by high energy CW laser to specifically study the laser-induced damage. Results show that laser parameters including power density and irradiation duration have an obvious effect on the damage. The poor graphite structure of residual char has a slight improvement under laser irradiation. The mixture of residual char and melted glass fiber can cover the surface of ablation region and prevent from oxidation. According to the micro-morphology and element analysis, the current paper gives a good understanding to the high energy laser-induced damage mechanism of the polybenzoxazine-based composites.